2013
DOI: 10.1098/rsbl.2013.0679
|View full text |Cite
|
Sign up to set email alerts
|

Humble origins for a successful strategy: complete enrolment in early Cambrian olenellid trilobites

Abstract: Trilobites are typified by the behavioural and morphological ability to enrol their bodies, most probably as a defence mechanism against adverse environmental conditions or predators. Although most trilobites could enrol at least partially, there is uncertainty about whether olenellids-among the most phylogenetically and stratigraphically basal representatives-could perform this behaviour because of their poorly caudalized trunk and scarcity of coaptative devices. Here, we report complete-but not encapsulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
(83 reference statements)
1
25
1
Order By: Relevance
“…He focuses on three species of Redlichia with inverted elements and describes scenarios for each specimen that require partial enrolment of the specimen during ecdysis. This link between ecdysial moult configurations and enrolment behaviour was in contrast to previous suggestions that Cambrian micropygous trilobites were rigid and unable to enrol (Harrington, 1959;Bergström, 1973), although later studies have shown that at least flexing, if not entire enrolment, was possible in these trilobites (Esteve et al, 2011Ortega-Hernández et al, 2013). McNamara (1986) stresses that inversions in Redlichia were "the exception, rather than the rule" (pg.…”
Section: Ecdysis In Redlichiidacontrasting
confidence: 77%
“…He focuses on three species of Redlichia with inverted elements and describes scenarios for each specimen that require partial enrolment of the specimen during ecdysis. This link between ecdysial moult configurations and enrolment behaviour was in contrast to previous suggestions that Cambrian micropygous trilobites were rigid and unable to enrol (Harrington, 1959;Bergström, 1973), although later studies have shown that at least flexing, if not entire enrolment, was possible in these trilobites (Esteve et al, 2011Ortega-Hernández et al, 2013). McNamara (1986) stresses that inversions in Redlichia were "the exception, rather than the rule" (pg.…”
Section: Ecdysis In Redlichiidacontrasting
confidence: 77%
“…Well-pre served trilobites, bur ied in life po si tion in heterolithic muddy-silty-sandy rocks in South China were noted by Degan et al (1995). Com pletely pre served and en rolled trilobites were re corded from the Cam brian of Green land (Geyer and Peel, 2011) and Can ada (Ortega-Hernández et al, 2013). Other oc cur rences of trilobites pre served in situ with their burrows, such as Thalassinoides nets with Asaphus raniceps, are known from car bon ate fa cies of the Swed ish Or do vi cian (Cherns et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This abil ity was very use ful and ef fec tive as de fence against pred a tors and also stress ful en vi ron ment con di tions. Such be hav ior in trilobites has been doc u mented from the Early Cam brian on wards (Ortega-Hernández et al, 2013 and ref er ences cited there).…”
Section: Introductionmentioning
confidence: 99%
“…, , ; Ortega‐Hernández et al . ; Esteve & Yuan ). Herein, we present two common Ordovician trilobites, Neseuretus Hicks (), and Placoparia Hawle & Corda ().…”
mentioning
confidence: 98%
“…Barrande 1852; Verneuil & Barrande 1855;Airaghi 1902). Nevertheless, what has not been evident until quite recently is that the group shows numerous different styles of enrolment that evolved separately in various lineages, independently of the basic body plans that characterize the major taxonomic groups (Esteve et al 2010(Esteve et al , 2012Ortega-Hern andez et al 2013;Esteve & Yuan 2017). Herein, we present two common Ordovician trilobites, Neseuretus Hicks (1875), and Placoparia Hawle & Corda (1847).…”
mentioning
confidence: 99%